The impact of obstructive sleep apnea on the remodeling of the immune system and its clinical significance - LI Jieqiong, XIAO Yi (Jichu yixue yu linchuang, 2025)
Obstructive sleep apnea (OSA) is a multifactor respiratory disorder characterized by recurrent episodes of airway collapse, leading to intermittent hypoxemia, hypercapnia, and sleep fragmentation. Intermittent hypoxia (IH) has profound effects on various body systems, particularly the immune system. Additionally, the suppression of the related inflammatory molecules mitigates IH-induced inflammation and tissue injury, presenting new potential targets for treating OSA-related complications. This review aims to explore the mechanisms by which OSA reshapes the immune system and its clinical significance.